Zintkala Woihanbla (Bird Dreams): Drifting and Other Decolonial Performances for Survival and Prison Abolition: (Urdimento - Revista de Estudos em Artes Cênicas, 2020)
Scholarship has often overlooked how Native Americans, who are disproportionately incarcerated, have developed tactics to cope with long-term imprisonment. Drawing on the authors’ correspondences and conversations, this essay features decolonial performances for survival and prison abolition, which George Blue Bird (Oglala Lakota) has enacted within conditions of carceral violence. These interlocking tactics are 1. Nurturing connections with more-than-humans; 2. “drifting”, Blue Bird’s term for imagining, traveling, and inhabiting other realms; and 3. Activating freedom and futurities. Ultimately, we focus on that these tactics and Lakota epistemologies offer the prison abolition movement.
Keywords: Artes de corrección; Colonialismo; Prisão; Performance; Abolição; Antropocentrismo; Enfrentamento